Assessment feedback in examiner reports on master's dissertations in translation studies - Man, Deliang; Xu, Yiqin; Chau, Meng Huat; O'Toole, John Mitchell; Shunmugam, Krishnavanie (Elsevier, 2020)
Assessment is a crucial part of degree programmes in higher education. While previous research has been primarily concerned with PhD thesis assessment practice in western countries, this article considers the focus and assessment criteria of 40 examiner reports on master's dissertations in translation studies at a Chinese university. The results indicate that these examiners structured their reports in four rhetorical moves: ‘preparing the candidate for a decision’, ‘expressing an evaluation’, ‘conveying the decision’, and ‘making recommendations’. These examiners appeared to place more emphasis on the expression of ideas, rather than on the accuracy and originality of those ideas. They apparently adopted flexible working criteria, assessing the dissertations based on institutional requirements and on their own experience. This article concludes with a discussion of implications for dissertation writing. © 2019 Elsevier Ltd